2011
DOI: 10.1002/pts.963
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Selected Plant Extracts and Application in Packaging as Antioxidant Cellulose‐Based Films for Vegetable Oil

Abstract: Selected plant extracts including cinnamon, clove, ginger, green tea and thyme were investigated for their antioxidant activity by using both -carotene-linoleate bleaching agar well diffusion and -carotene-linoleate bleaching broth assays, and for radical scavenging activity against free radicals using a 2,2-diphenyl-1picrylhydrazyl assay. Undiluted plant extracts (except ginger oil) showed a yellow zone of -carotene ranging from 15.3 to 38.2mm in diameter. At a concentration of 50LmL -1 , thyme yielded the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…After 8 weeks under accelerated storage conditions, the antioxidant effects of clove oil yielded inhibition rate of 10.6%. This study showed the potential use of plant extracts (cinnamon and clove oil) as antioxidants for food packaging application (Phoopuritham et al, 2012).…”
Section: Packaging Filmmentioning
confidence: 82%
“…After 8 weeks under accelerated storage conditions, the antioxidant effects of clove oil yielded inhibition rate of 10.6%. This study showed the potential use of plant extracts (cinnamon and clove oil) as antioxidants for food packaging application (Phoopuritham et al, 2012).…”
Section: Packaging Filmmentioning
confidence: 82%
“…For nanobiopolymers films, emulsion A (4 ml) was added to test tubes containing nanobiopolymers, cut into 2 × 2 cm pieces (Phoopuritham, Thongngam, Yoksan, & Suppakul, ). Two solutions, one with no antioxidant (control) and the other without β‐carotene (emulsion B — white), were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Structures such as porous solid food can be protected by the migration of volatile active agents in antioxidant packaging systems (Figure 6.2B). Antioxidants of natural origin that have been studied in the development of antioxidant packaging include tocopherol, ascorbic acid, curcumin, tyrosine, essential oils and plant extracts of barley husks, borage, cinnamon, citronella, clove, ginger, green tea, marigold, murta leaves, rosemary, oregano, and thyme (Camo et al, 2008;Colín-Chávez et al, 2012;Gemili et al, 2010;Gimenez et al, 2011;Gutiérrez et al, 2012;Nerin et al, 2008;Phoopuritham et al, 2012;Sonkaew et al, 2012;Wessling et al, 1999). Scavenging of vapor-phase radicals has been suggested as a possible mechanism.…”
Section: Antioxidant Packagingmentioning
confidence: 99%
“…Synthetic antioxidants of BHA and BHT, which have been used to protect polymers during film manufacture, have some degree of volatility and could migrate to the contained solid food through the gas phase (Miltz et al, 1988;Wessling et al, 2001). Antioxidant films from rosemary, oregano, clove, and cinnamon could play a role in inhibiting oxidative quality deterioration for systems with both indirect and direct contact between the packaged food and the film (Camo et al, 2008;Nerin et al, 2008;Phoopuritham et al, 2012). Antioxidant films from rosemary, oregano, clove, and cinnamon could play a role in inhibiting oxidative quality deterioration for systems with both indirect and direct contact between the packaged food and the film (Camo et al, 2008;Nerin et al, 2008;Phoopuritham et al, 2012).…”
Section: Antioxidant Packagingmentioning
confidence: 99%